Utilização de um sistema de informações geográficas associado à equação universal de perda de solo no planejamento do ecoturismo no Município de Santo Antônio do Pinhal - SP - Rosalen, David Luciano (2002)
Ecoturism hás been blunting inside the industry of the tourism as a promissing revenue source for the local population. However, to make one of its main objectives be accomplished, wich is to help keeping the natural resources, that activity should be planned inside a keeping context. Inside this context, the soil conservation is one of the main features because the soil is the physical, chemical and biological support of the vegetation, either natural or exotic. To conservation it, it s necessary to indentify the erosinal areas, wich can be accomplished by the use of empirical models. Among the different existent models, the Universal Soil Loss Equation (USLE) is one of the most remarkable and used in the use of Geografic Information System (GIS), the applying of this model, by the use of this computacionsl tool, has almost been turned to be necessary due to the speed and to the easiness of simulating different sceneries. Therefore, the present work, through the development of a simple methodology, applied the model EUPS through GIS in the area of Santo Antônio do Pinhal-SP, wich has developed ecoturism activities through the use of trails. Information of the physical site (geology, geomorphology, pedology and topography), area of acceptable and non-acceptable soil losses, areas of everlasting keeping and roads, and the topographical profiles of ecoturism trails of the area, were mixed. The results showed the great weakness of the area when it comes to erosive processes, the unfitness of roads and profiles of the trails concerning the control of erosive processes and the importance of the ecoturism as a revenue alternative for the local population, due the restrict agronomy aptitude of the area.